Urgensi pengembangan teknologi finansial (fintech) dalam meningkatkan efisiensi operasional bank syariah - Aisyah, Dwi Danty (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the urgency of developing financial technology (fintech) in enhancing the operational efficiency of Islamic banks in Indonesia. Amid the digital transformation of the financial services sector, fintech has emerged as a strategic solution that not only accelerates transaction and service processes but also reduces operational costs and expands access to Sharia-compliant financial services. Using a qualitative descriptive approach and literature review from credible sources, the study finds that the adoption of fintech tools such as digital banking, Sharia-based peer-to-peer lending, e-wallets, and halal crowdfunding significantly improves the efficiency and competitiveness of Islamic banking. Case studies of digital application implementations by several Islamic banks demonstrate the success of technology-driven service transformation while maintaining Sharia principles. However, challenges remain, including limited digital infrastructure, a shortage of human resources with dual expertise in technology and Islamic law, and regulatory frameworks that have yet to fully support such innovation. Therefore, the development of Sharia fintech requires strong cross-sector collaboration to establish a modern, efficient, and sustainable Islamic financial ecosystem.